Craniorachischisis: first case reported in Madagascar - Rabarikoto, Hary F.; Rakotozanany, Patrick S.; Tsifiregna, Rosa L.; Ratovondrainy, Willy; Randriambololona, Domoina M. A. (International Journal of Research in Medical Sciences, 2018)
Craniorachischisis is the most severe type of neural tube defect in which almost the entire brain and spinal cord remain open. We report a case in a female fetus born at gestational week 38, with both anencephaly and open spina bifida. It was the second pregnancy of a 26-year-old woman. The first pregnancy had to be interrupted by a medical termination at 18th gestational week because of an anencephaly. We aim to report the first case documented in Madagascar.